A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic - Rodrigues, Thaiana G. A.; Alves-Júnior, Flavio A.; Cardoso, Irene A. (Zootaxa, 2018)
The genus Pasiphaea Savigny, 1816 (Caridea: Pasiphaeidae) includes 71 species, of which vast majority inhabit in the meso or bathypelagic zones in the world oceans. A new species is described herein, sampled during the project "ABRACOS 2" (Acoustic along the BRazilian COast) nearby the Rocas Atoll and Fernando de Noronha Archipelago, in Brazilian waters. Pasiphaea antea n. sp. appears close to Pasiphaea dorsolineatus Komai & Chan, 2012 described from off Hawaii, but is distinguished from the latter by the different shape of the rostrum, the mid-dorsal line of the carapace sharply carinate in the anterior half, and the possession of more numerous spiniform setae on the meri of the pereopods 1 and 2. This is the third species known from the southwestern Atlantic.